Ratios of bottom meson branching fractions involving J/psi mesons and determination of b quark fragmentation fractions - Abe, F; Akimoto, H; Akopian, A; Albrow, MG; Amendolia, SR; Amidei, D; Antos, J; AnwayWiese, C; Aota, S; Apollinari, G; Asakawa, T; Ashmanskas, W; et al. (1996)
We report a measurement of the ratios of the decay rates of the B+, B0, and Bs 0 mesons into exclusive final states containing a J/ψ meson. The final states were selected from 19.6 pb-1 of pp̄ collisions recorded by the Collider Detector at Fermilab. These data are interpreted to determine the b quark fragmentation fractions fu, fd, and fs. We also determine the branching fractions for the decay modes B+ → J/ψK+, B+ → J/ψK*(892)+, B0 → J/ψK0, B0 → J/ψK*(892)0, and Bs 0 → J/ψφ(1020). We discuss the implications of these measurements to B meson decay models. © 1996 The American Physical Society.